Impact of Demographic, Socioeconomic and Psychological Factors on Glycemic Self-Management in Adults with Type 2 Diabetes Mellitus - Alicia Alicia Gonzalez Zacarias; Ana Mavarez-Martinez; Carlos E Arias Morales; Nicoleta Stoicea; Barbara Rogers (Frontiers Media S.A., 2016)
Diabetes Mellitus (DM) is reported as one of the most complex chronic diseases worldwide. In the United States, Type 2 Diabetes Mellitus (T2DM) is the seventh leading cause of morbidity and mortality. Individuals with diabetes require lifelong personal care to reduce the possibility of developing long-term complications. A good knowledge of diabetes risk factors, including obesity, dyslipidemia, hypertension, family history of DM, and sedentary lifestyle, play an essential role in prevention and treatment. Also, socio-demographic, economic, psychological, and environmental factors are directly and indirectly associated with diabetes control and health outcomes. Our review intends to analyze the interaction between demographics, knowledge, environment, and other diabetes-related factors based on an extended literature search, and to provide insight for improving glycemic control and reducing the incidence of chronic complications.